Method for depositing diamond film on surface of zirconia ceramic and product and application thereof

By depositing an intermediate transition layer on the surface of zirconia ceramics and performing carbonization heat treatment, the film base mismatch caused by the mismatch of the thermal expansion coefficient between the diamond film and the zirconia ceramic substrate is solved, and the firm connection between the diamond film and the zirconia ceramic substrate is achieved, and the wear resistance and corrosion resistance of zirconia ceramics is improved.

CN119592921APending Publication Date: 2025-03-11QIANWAN INST OF CNITECH +1

Patent Information

Application Number
CN202411779046.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When diamond film is deposited on the surface of zirconia ceramics, due to the mismatch of thermal expansion coefficients, it is easy to cause huge thermal stress to the diamond coating during cooling of high deposition temperatures, which will fall off and cause film base mismatch.

Method used

Using hot wire chemical vapor deposition and physical vapor deposition technology, an intermediate transition layer (such as silicon, titanium or chromium film) is first deposited on the zirconia ceramic substrate, and then the nucleation density of the phytograft is increased by carbonization heat treatment to achieve high binding force between the diamond and the transition layer. Finally, ultrasonic oscillation of the crystal grains in the nanodiamond suspension is ultrasonic to prepare diamond films.

Benefits of technology

The firm connection between the diamond film and the zirconia ceramic substrate is achieved, the film-based matching problem is overcome, and the wear resistance and corrosion resistance of zirconia ceramics is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592921A_ABST
    Figure CN119592921A_ABST
Patent Text Reader

Abstract

The invention discloses a method for depositing a diamond film on the surface of zirconia ceramic and a product and application of the diamond film, and belongs to the technical field of surface treatment.The method comprises the steps that 1, a zirconia ceramic substrate is pretreated; (2) depositing a transition layer on the zirconia ceramic substrate treated in the step (1) through magnetron sputtering, wherein the transition layer is a silicon film, a titanium film or a chromium film; (3) carrying out carbonization heat treatment on the surface of the transition layer through hot filament chemical vapor deposition; and (4) placing the zirconia ceramic substrate treated in the step (3) in an ethanol suspension of nano-diamond, performing ultrasonic oscillation and crystal planting, taking out the zirconia ceramic substrate, drying, and preparing the diamond film by utilizing hot filament chemical vapor deposition. The method is simple, efficient, good in controllability and high in repetition rate, firm connection between the diamond film and the zirconia ceramic can be achieved, the film-substrate matching problem is solved, and the abrasion resistance and corrosion resistance of the zirconia ceramic substrate are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface treatment, and in particular to a method for depositing a diamond film on the surface of a zirconia ceramic, and a product and application thereof. Background Art

[0002] Diamond is the hardest substance naturally existing in nature. Graphite can form artificial diamond under high temperature and high pressure. In order to improve the hardness, wear resistance, corrosion resistance and reduce the friction coefficient of the material surface and extend its service life, a diamond coating is usually prepared on the material surface. The preparation process of diamond coating is mainly chemical vapor deposition (CVD), including microwave plasma chemical vapor deposition, hot wire chemical vapor deposition and DC arc plasma jet chemical vapor deposition. According to different preparation methods, polycrystalline diamond can be divided into micron-level, nano-level and ultrafine nano-level diamond according to different grain sizes. Diamond coating has been widely used in cutting tools, automotive parts, medical equipment, electronic devices and other fields. For example, the Chinese patent document with publication number CN106119846A discloses a method for preparing a corrosion-resistant and wear-resistant coating on the surface of a magnesium alloy. The method first performs micro-arc oxidation on the pretreated magnesium alloy surface to generate a 20-50μm ceramic layer on the surface of the magnesium alloy; then the ceramic layer is mechanically polished with CH 4 A 10nm to 10μm diamond film layer is deposited on a ceramic layer using microwave plasma vapor deposition as a carbon source. The Chinese patent document with publication number CN106591799A discloses a method for preparing a diamond coating and a diamond coated blade. The invention first performs an alkali washing treatment on a cemented carbide substrate, and obtains a clean cemented carbide substrate after washing and drying; the clean cemented carbide substrate is placed in a copper sulfate solution with a mass fraction of 10% to 20% for 5 to 30 minutes to obtain a cemented carbide substrate containing a copper transition layer; the cemented carbide substrate containing a copper transition layer is placed in a nano-diamond organic suspension for ultrasonic cleaning, and then a diamond coating is prepared on its surface by chemical vapor deposition. The introduction of the diamond coating has a protective effect on the substrate, improving its wear resistance and service life.

[0003] Zirconia ceramics have the characteristics of high hardness, high strength, good corrosion resistance, excellent thermal stability, insulation performance and biocompatibility, and are ideal wear-resistant materials for use in various harsh environments. However, in harsh environments such as ocean, high vacuum, high humidity, radiation, and extreme working conditions such as high speed, heavy load, and impact, various failure problems such as friction, corrosion, and fracture of equipment parts are more serious. The mechanical properties and stability of zirconia ceramic materials cannot fully meet the needs of harsh working conditions. Surface strengthening technology is one of the effective means to improve the wear resistance of the base material. Introducing diamond coating on the surface of zirconia ceramics helps to improve its wear resistance and corrosion resistance.

[0004] However, the thermal expansion coefficient of zirconia ceramics (10.5×10 -6 / K) is higher (compared with steel 12×10 -6 / K, which is quite different from the thermal expansion coefficient of diamond (1.3×10 -6 / K), therefore, when depositing diamond coating on the surface of zirconia ceramics, it is easy for the thermal expansion coefficients between diamond and substrate to mismatch, resulting in huge thermal stress inside the film during the cooling process of the high deposition temperature, and then the diamond coating will fall off. Zirconia ceramics have a high thermal expansion coefficient, and the diamond coating is prone to film-substrate mismatch when it is prepared on the surface of zirconia ceramics. Film-substrate mismatch refers to the interface mismatch between the film and the substrate. This mismatch may lead to an increase in the interface barrier, thereby affecting the nucleation and growth of the film, and may cause the coating to fall off. Therefore, if a diamond film is to be deposited on the surface of zirconia ceramics, solving the film-substrate matching problem is the key point. Summary of the invention

[0005] In view of the limited film-substrate matching problem of diamond-modified zirconia ceramics, the present invention provides a method for depositing a diamond film on the surface of zirconia ceramics. The method is simple and efficient, has good controllability and high repetition rate, can achieve a firm connection between the diamond film and the zirconia ceramic, and improve the wear and corrosion resistance of the zirconia ceramic substrate.

[0006] The specific technical solutions adopted are as follows:

[0007] A method for depositing a diamond film on a surface of a zirconium oxide ceramic comprises the following steps:

[0008] (1) pretreating a zirconia ceramic substrate to obtain a clean and dried zirconia ceramic substrate;

[0009] (2) depositing a transition layer on the zirconia ceramic substrate treated in step (1) by magnetron sputtering, wherein the transition layer is a silicon film, a titanium film or a chromium film;

[0010] (3) performing carbonization heat treatment on the transition layer surface by hot wire chemical vapor deposition;

[0011] (4) placing the zirconia ceramic substrate treated in step (3) in an ethanol suspension of nanodiamonds for ultrasonic vibration to plant crystals, taking out and drying it, and then using hot wire chemical vapor deposition to prepare a diamond film.

[0012] The method of the present invention combines hot wire chemical vapor deposition and physical vapor deposition technology to introduce an intermediate transition layer. On the one hand, the transition layer has good bonding with the zirconia ceramic substrate, while still ensuring good performance (no surface changes and no shedding) under high temperature thermal cycles (simulating diamond growth environment), thereby achieving a firm connection with the zirconia ceramic substrate. On the other hand, the transition layer must achieve a strong bonding with the diamond layer. By carbonizing the surface of the transition layer, the density of plant nucleation can be increased, thereby achieving a high bond between the diamond and the transition layer. The present invention deposits a diamond film on the surface of the zirconia ceramic, successfully preparing diamond-modified zirconia ceramics, effectively improving the wear resistance and corrosion resistance of the zirconia ceramic substrate, and overcoming the film-substrate matching problem.

[0013] The substrate can be selected from a ceramic sealing ring, a ceramic substrate, a ceramic knife and the like.

[0014] Specifically, the pretreatment method includes: ultrasonically cleaning the zirconia ceramic substrate using acetone, ethanol and deionized water in sequence to remove dust and impurities on the surface of the substrate; and drying with nitrogen after cleaning.

[0015] Preferably, in step (2), the parameters of magnetron sputtering deposition include: a vacuum degree of 1×10 -4 Pa or less, the deposition power is 80-150 W, the pressure is 1.0-1.5 Pa, the temperature is 250-500°C, the deposition time is 0.1-2 h, and further 1-2 h.

[0016] Conducting simulated thermal cycle experiments on the transition layer can verify the effect of high temperature on its bonding strength. The transition layer deposited by magnetron sputtering under the above-mentioned preferred parameters not only has good bonding strength with the zirconia ceramic substrate, but also maintains good stability under high-temperature thermal cycle conditions (simulating diamond growth environment).

[0017] Preferably, in step (3), the zirconia ceramic substrate with the transition layer is placed in a hot wire chemical vapor deposition device for carbonization heat treatment. During the treatment, the methane flow rate is 8 to 12 mL / min, the hydrogen flow rate is 200 to 400 mL / min, the hot wire power is 3000 to 3600 W, and the heat treatment time is 10 to 30 min.

[0018] Specifically, in step (4), the particle size of the nano-diamond is 1 to 100 nm, the concentration of the nano-diamond ethanol suspension is 0.1 to 5 wt %; and the ultrasonic oscillation time is 0.1 to 1 h.

[0019] Preferably, in step (4), tantalum wire is used to prepare the diamond film by hot wire chemical vapor deposition, and the process parameters are: methane flow rate is 8-12 mL / min, hydrogen flow rate is 200-400 mL / min, hot wire power is 2800-3600 W, and deposition time is 2-15 h.

[0020] The invention also provides diamond-modified zirconia ceramics prepared by the method of depositing a diamond film on the surface of the zirconia ceramics.

[0021] Specifically, the diamond-modified zirconia ceramic comprises a zirconia ceramic substrate and a transition layer and a diamond layer sequentially deposited thereon, the thickness of the transition layer is 0.1 to 4 μm, and the thickness of the diamond layer is 3 to 25 μm.

[0022] The present invention also provides a method for depositing a diamond film on the surface of the zirconia ceramic or application of the diamond-modified zirconia ceramic in the field of surface protection.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention combines chemical vapor deposition and physical vapor deposition to prepare a diamond coating on the surface of zirconia ceramics, thereby improving the wear resistance and corrosion resistance of the zirconia ceramic substrate, and the bonding force between the diamond coating and the zirconia ceramic substrate is strong (characterized by scratch test).

[0025] (2) The diamond-modified zirconia ceramics prepared by the present invention can effectively improve the friction performance of a single dynamic sealing ring under various friction conditions such as dry friction, boundary lubrication, and strong corrosive media, and can be applied to complex and changeable service environments.

[0026] (3) The present invention introduces an intermediate transition layer, which not only has good bonding strength with the zirconia ceramic substrate, but also does not peel off or collapse on the surface under high-temperature thermal cycle conditions (simulating the diamond growth environment), thereby ensuring good performance and achieving a firm connection with the zirconia ceramic substrate; and there is good bonding strength between the transition layer and the diamond coating (the density of crystal nucleation is increased by carbonizing the transition layer surface, thereby achieving high bonding strength between the diamond and the transition layer).

[0027] (4) The preparation method of the diamond-modified zirconia ceramics in the present invention is simple, efficient, well controllable and has a high reproducibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a flow chart of a method for depositing a diamond film on a zirconia ceramic surface.

[0029] Figure 2These are the optical images and SEM images of the transition layer deposited on the zirconia ceramic substrate in Example 1 before and after the thermal cycling test, wherein (a) and (b) are the optical images and SEM images before the thermal cycling test of the transition layer, respectively, and (c) and (d) are the optical images and SEM images after the thermal cycling test of the transition layer, respectively.

[0030] Figure 3 It is a diagram showing the effect of carbonization heat treatment on crystal planting in Example 1, wherein (a) is a surface SEM image of the crystal planted without carbonization heat treatment, (b) is a surface C element distribution map in (a), (c) is a surface SEM image of the crystal planted after carbonization heat treatment, and (d) is a surface C element distribution map in (c).

[0031] Figure 4 This is the surface SEM morphology of the diamond-modified zirconia ceramic in Example 1. DETAILED DESCRIPTION

[0032] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description through specific embodiments. In the following description, many specific details are set forth in order to fully understand the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.

[0033] The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer. The contents not described in detail in this specification belong to the prior art known to professionals in the field. The experimental materials used in the following examples, unless otherwise specified, can be purchased from conventional biochemical reagent companies.

[0034] In the embodiment, the method flow chart of depositing diamond film on the surface of zirconium oxide ceramic is as follows: Figure 1 As shown, the particle size of the nano-diamond in the nano-diamond ethanol suspension used is 10 to 100 nm.

[0035] Example 1

[0036] (1) Substrate pretreatment: The zirconia ceramic substrate needs to be pretreated before depositing the transition layer. Specifically, the zirconia ceramic dynamic sealing ring is cleaned with acetone, ethanol, and deionized water for 10 to 30 minutes in sequence to remove dust and impurities on the substrate surface; after cleaning, it is blown dry with nitrogen for later use.

[0037] (2) Preparation of transition layer on substrate surface and verification of high temperature thermal stability: The transition layer was deposited on the zirconia ceramic substrate treated in step (1) by magnetron sputtering. A DC power supply was used for deposition and the vacuum degree was maintained at 7×10 -4 Pa, the deposition power is 120W, the pressure is 1.0Pa, the temperature is 300℃, and the deposition time is 1h to obtain a silicon film as a transition layer; after the transition layer is deposited on the zirconia ceramic substrate, in order to verify the effect of high temperature on its bonding strength, a tubular furnace is used to perform high-temperature thermal cycle treatment on the zirconia substrate after Si coating. The parameters of the tubular furnace are an initial temperature of 20℃, a heating time of 60min, a heating time of 650℃, a heat preservation time of 300min, and finally a cooling down from 650℃; through Figure 2 As can be seen from (a)-(d) in the figure, the transition layer silicon film still maintains good stability under the above-mentioned simulated thermal cycling conditions, and its morphology does not change significantly.

[0038] (3) Preparation of diamond coating: The zirconium oxide ceramic substrate with the transition layer deposited was placed in a hot wire chemical vapor deposition device for carbonization heat treatment. During the treatment, the methane flow rate was 12 mL / min, the hydrogen flow rate was 400 mL / min, the hot wire power was 3600 W, and the heat treatment time was 20 min. The sample after carbonization heat treatment was placed in a 5wt% nanodiamond ethanol solution for ultrasonic vibration and crystal planting for 1 hour, and the sample was taken out and blown dry. The crystal planting effect was characterized, and a transition layer without carbonization heat treatment was set as a control. The results are shown in the figure. Figure 3 As shown in (a)-(d) in the figure, it can be seen that carbonization heat treatment can increase the density of crystal nucleation, thereby achieving a high bonding force between diamond and the transition layer.

[0039] Finally, the samples after crystal planting were placed in a hot wire chemical vapor deposition device for diamond film deposition. The hot wire used was tantalum wire. During deposition, the methane flow rate was 12 mL / min, the hydrogen flow rate was 400 mL / min, the hot wire power was 3600 W, and the deposition time was 5 h to prepare diamond-modified zirconia ceramics.

[0040] The diamond-modified zirconia ceramic prepared in this embodiment includes a zirconia ceramic substrate, a Si layer and a diamond layer. The surface SEM image thereof is as follows: Figure 4 shown.

[0041] Example 2

[0042] (1) Substrate pretreatment: The zirconia ceramic substrate needs to be pretreated before depositing the transition layer. Specifically, the zirconia ceramic dynamic sealing ring is cleaned with acetone, ethanol, and deionized water for 10 to 30 minutes in sequence to remove dust and impurities on the substrate surface; after cleaning, it is blown dry with nitrogen for later use.

[0043] (2) Preparation of transition layer on substrate surface and verification of high temperature thermal stability: The transition layer was deposited on the zirconia ceramic substrate treated in step (1) by magnetron sputtering. A DC power supply was used for deposition and the vacuum degree was maintained at 1×10 -4 Pa below, the deposition power is 150W, the pressure is 1.0Pa, the temperature is 250℃, and the deposition time is 1h to obtain a titanium film as a transition layer; after the transition layer is deposited on the zirconia ceramic substrate, in order to verify the effect of high temperature on its bonding strength, the zirconia substrate after the Ti layer is plated is subjected to high-temperature thermal cycle treatment in a tubular furnace. The parameters of the tubular furnace are an initial temperature of 20℃, a heating time of 60min, a heating time of 650℃, a holding time of 300min, and finally a cooling down from 650℃; the results show that the transition layer titanium film still maintains good stability under the above-mentioned simulated thermal cycle conditions, and there is no obvious change in morphology.

[0044] (3) Preparation of diamond coating: Place the zirconium oxide ceramic substrate with the transition layer deposited on it into a hot wire chemical vapor deposition device for carbonization heat treatment. During the treatment, the methane flow rate is 12 mL / min, the hydrogen flow rate is 400 mL / min, the hot wire power is 3600 W, and the heat treatment time is 20 min. Place the sample after carbonization heat treatment into a 5wt% nanodiamond ethanol suspension for ultrasonic oscillation crystal planting for 1 hour, take out the sample, and blow dry. Finally, place the sample after crystal planting into a hot wire chemical vapor deposition device for diamond film deposition. The hot wire uses tantalum wire. During deposition, the methane flow rate is 10 mL / min, the hydrogen flow rate is 400 mL / min, the hot wire power is 3600 W, and the deposition time is 5 hours to prepare diamond-modified zirconium oxide ceramics.

[0045] The diamond-modified zirconia ceramic prepared in this embodiment includes a zirconia ceramic substrate, a Ti layer and a diamond layer. The thickness of the Ti layer is about 2-4 μm, and the thickness of the diamond layer is about 8 μm.

[0046] Example 3

[0047] (1) Substrate pretreatment: The zirconia ceramic substrate needs to be pretreated before depositing the transition layer. Specifically, the zirconia ceramic dynamic sealing ring is cleaned with acetone, ethanol, and deionized water for 10 to 30 minutes in sequence to remove dust and impurities on the substrate surface; after cleaning, it is blown dry with nitrogen for later use.

[0048] (2) Preparation of transition layer on substrate surface and verification of high temperature thermal stability: The transition layer was deposited on the zirconia ceramic substrate treated in step (1) by magnetron sputtering. A DC power supply was used for deposition and the vacuum degree was maintained at 2×10 -4Pa below, the deposition power is 100W, the pressure is 1.0Pa, the temperature is 300℃, and the deposition time is 1h to obtain a chromium film as a transition layer; after the transition layer is deposited on the zirconia ceramic substrate, in order to verify the effect of high temperature on its bonding strength, a tubular furnace is used to perform high-temperature thermal cycle treatment on the zirconia substrate after Cr coating. The tubular furnace parameters are an initial temperature of 20℃, a heating time of 60min, a heating time of 650℃, a holding time of 300min, and finally a cooling down from 650℃. The results show that the transition layer chromium film still maintains good stability under the above-mentioned simulated thermal cycle conditions, and there is no obvious change in morphology.

[0049] (3) Preparation of diamond coating: Place the zirconium oxide ceramic substrate with the transition layer deposited in a hot wire chemical vapor deposition device for carbonization heat treatment. During the treatment, the methane flow rate is 10 mL / min, the hydrogen flow rate is 400 mL / min, the hot wire power is 3600 W, and the heat treatment time is 20 min. Place the sample after carbonization heat treatment in a 5wt% nanodiamond ethanol suspension for ultrasonic crystal planting for 1 hour, take out the sample, and blow dry. Finally, place the sample after crystal planting in a hot wire chemical vapor deposition device for diamond film deposition. The hot wire uses tantalum wire. During deposition, the methane flow rate is 12 mL / min, the hydrogen flow rate is 400 mL / min, the hot wire power is 3600 W, and the deposition time is 5 hours to prepare diamond-modified zirconium oxide ceramics.

[0050] The diamond-modified zirconia ceramic prepared in this embodiment includes a zirconia ceramic substrate, a Cr layer and a diamond layer.

[0051] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for depositing a diamond film on a zirconia ceramic surface, characterized in that: The following steps are involved: (1) Pretreating the zirconia ceramic substrate; (2) depositing a transition layer on the zirconia ceramic substrate treated in step (1) by magnetron sputtering, wherein the transition layer is a silicon film, a titanium film or a chromium film; (3) performing carbonization heat treatment on the transition layer surface by hot wire chemical vapor deposition; (4) placing the zirconia ceramic substrate treated in step (3) in an ethanol suspension of nanodiamonds for ultrasonic vibration to plant crystals, taking out and drying it, and then using hot wire chemical vapor deposition to prepare a diamond film.

2. The method for depositing a diamond film on the surface of zirconia ceramics according to claim 1, characterized in that: The pretreatment method includes: ultrasonically cleaning the zirconia ceramic substrate with acetone, ethanol and deionized water in sequence, and drying it with nitrogen after cleaning.

3. The method for depositing a diamond film on the surface of zirconia ceramics according to claim 1, characterized in that: In step (2), the parameters of magnetron sputtering deposition include: vacuum degree of 1×10 -4 Pa, the deposition power is 80-150 W, the pressure is 1.0-1.5 Pa, the temperature is 250-500 ° C, and the deposition time is 0.1-2 h.

4. The method for depositing a diamond film on the surface of zirconia ceramics according to claim 1, characterized in that: In step (3), the zirconia ceramic substrate with the transition layer is placed in a hot wire chemical vapor deposition device for carbonization heat treatment. During the treatment, the methane flow rate is 8 to 12 mL / min, the hydrogen flow rate is 200 to 400 mL / min, the hot wire power is 3000 to 3600 W, and the heat treatment time is 10 to 30 min.

5. The method for depositing a diamond film on the surface of zirconia ceramics according to claim 1, characterized in that: In step (4), the particle size of the nano-diamond is 1 to 100 nm, the concentration of the nano-diamond ethanol suspension is 0.1 to 5 wt %; and the ultrasonic oscillation time is 0.1 to 1 h.

6. The method for depositing a diamond film on the surface of zirconia ceramics according to claim 1, characterized in that: In step (4), tantalum wire is used to prepare the diamond film by hot wire chemical vapor deposition, and the process parameters are: methane flow rate is 8-12 mL / min, hydrogen flow rate is 200-400 mL / min, hot wire power is 2800-3600 W, and deposition time is 2-15 h.

7. Diamond-modified zirconia ceramics obtained by the method for depositing a diamond film on the surface of zirconia ceramics according to any one of claims 1 to 6.

8. The diamond-modified zirconia ceramic according to claim 7, characterized in that: The invention comprises a zirconium oxide ceramic substrate and a transition layer and a diamond layer deposited in sequence thereon. The thickness of the transition layer is 0.1 to 4 micrometers, and the thickness of the diamond layer is 3 to 25 micrometers.

9. The method for depositing a diamond film on the surface of a zirconia ceramic according to any one of claims 1 to 6 or the use of the diamond-modified zirconia ceramic according to claim 7 or 8 in the field of surface protection.

Citation Information

Patent Citations

  • Method for preparing corrosion-resistant and abrasion-resistant coating on surface of magnesium alloy

    CN106119846A

  • Preparation method of diamond coating layer and diamond coating layer blade

    CN106591799A

Cited By

  • Preparation method of diamond coating on surface of textured zirconium oxide substrate

    CN121248324A